2012
DOI: 10.5501/wjv.v1.i6.174
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment to prevent chronic hepatitis B or C-related hepatocellular carcinoma

Abstract: Antiviral treatment is the only option to prevent or defer the occurrence of hepatocellular carcinoma (HCC) in patients chronically infected with hepatitis B virus (HBV) or hepatitis C virus (HCV). The approved medication for the treatment of chronic HBV infection is interferon-α (IFNα) and nucleos(t)ide analogues (NAs), including lamivudine, adefovir dipivoxil, telbivudine, entecavir and tenofovir disoproxil fumarate. IFNα is the most suitable for young patients with less advanced liver diseases and those inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 92 publications
1
25
0
Order By: Relevance
“…Although the relationship between HBV infection and HCC has not been fully described, antiviral treatments for HBV infections have been proven to reduce HCC risk in patients with chronic HBV infection, with or without the presence of cirrhosis [12]. It was reported that antiviral treatments using oral nucleoside analogs can result in up to a 78% decrease in HCC incidence, especially in HBeAg-positive patients, but long-term continuous treatment with nucleoside or nucleotide analogs (NAs) can cause drug resistance due to the mutations in HBV polymerase [13][14][15]. Lai et al pointed out that antiviral treatments using nucleoside analogs appear to be more effective in reducing the risk of HCC development, while the effect of interferon-α (IFN-α) antiviral treatment is likely to be limited to patients with cirrhosis [16].…”
Section: Antiviral Treatment In Hcc Preventionmentioning
confidence: 99%
“…Although the relationship between HBV infection and HCC has not been fully described, antiviral treatments for HBV infections have been proven to reduce HCC risk in patients with chronic HBV infection, with or without the presence of cirrhosis [12]. It was reported that antiviral treatments using oral nucleoside analogs can result in up to a 78% decrease in HCC incidence, especially in HBeAg-positive patients, but long-term continuous treatment with nucleoside or nucleotide analogs (NAs) can cause drug resistance due to the mutations in HBV polymerase [13][14][15]. Lai et al pointed out that antiviral treatments using nucleoside analogs appear to be more effective in reducing the risk of HCC development, while the effect of interferon-α (IFN-α) antiviral treatment is likely to be limited to patients with cirrhosis [16].…”
Section: Antiviral Treatment In Hcc Preventionmentioning
confidence: 99%
“…However, the antiviral efficacy of IFN-based drugs is restricted to less than 40% (9,10). Second, nucleos(t)ide analogs, including lamivudine (LMV), adefovir, entecavir (ETV), tenofovir, and telbivudine suppress HBV by inhibiting the viral reverse transcriptase (11,12). Although they can provide significant clinical improvement, long term therapy with nucleos(t)ide analogs often results in the selection of drug-resistant mutations in the target gene, which limits the treatment outcome.…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…Potent antiviral agents are medicines which may provide long-term HBV DNA suppression and improvement of cirrhosis with quite low resistance rates. Additionally, their long-term use may decrease the risk of HCC development (19). The most commonly given drugs in our patient group were tenofovir and entecavir.…”
Section: Discussionmentioning
confidence: 92%